Clostridium butyricum Ameliorates Salmonella Enteritis Induced Inflammation by Enhancing and Improving Immunity of the Intestinal Epithelial Barrier at the Intestinal Mucosal Level - Zhao, Xiaonan; Yang, Jie; Ju, Zijing; Wu, Jianmin; Wang, Lili; Lin, Hai; Sun, Shuhong (Frontiers in Microbiology, 2020)
This study was aimed to investigate the effects of Clostridium butyricum (C. butyricum) immunity and intestinal epithelial barrier function at the intestinal mucosal level, by using Salmonella enteritidis (S. enteritidis) to infect specific-pathogen-free (SPF) chickens and intestinal epithelial cells (IEC). We found that C. butyricum could decrease cytokine levels (IFN-γ, IL-1β, IL-8 and TNF-α) via the TLR4-, MyD88-, and NF-κB-dependent pathways in intestinal tissues and intestinal epithelial cells. Additionally, C. butyricum could attenuate bacteria-induced intestinal damage and increase the expression level of muc-2 and ZO-1 in the intestine and intestinal epithelial cells. Furthermore, C. butyricum altered the intestinal microbial composition, increased the diversity of the bacterial communities in the cecum of Salmonella-infected chickens. In conclusion, C. butyricum effectively attenuated inflammation and epithelial barrier damage, altered the intestinal microbial composition, increased the diversity of the bacterial communities in the intestine of Salmonella-infected chickens. The result suggests that C. butyricum might be an effective and safe therapy for the treatment of Salmonella infection.